Dialogical social theory - Levine, Donald Nathan (Routledge, 2018)
In his final work, Donald N. Levine, one of the great late-twentieth-century sociological theorists, brings together diverse social thinkers. Simmel, Weber, Durkheim, Parsons, and Merton are set into a dialogue with philosophers such as Hobbes, Smith, Montesquieu, Comte, Kant, and Hegel and pragmatists such as Peirce, James, Dewey, and McKeon to describe and analyze dialogical social theory. This volume is one of Levine’s most important contributions to social theory and a worthy summation of his life’s work.